AKTIVITAS ANTIBAKTERI EKSTRAK TUMBUHAN LUMUT HATI (Marchantia paleacea) TERHADAP BAKTERI PATOGEN DAN PERUSAK PANGAN [Antibacterial Activity of Liverwort (Marchantia paleacea) Extract on Pathogenic and Food Spoilage Bacteria] - Reza Fadhilla; Eka Aditya Iskandar; Harsi Dewantari Kusumaningrum (Jurnal Teknologi dan Industri Pangan, 2012)
Liverwort (Marchantia paleacea) from Cibodas Botanical Garden Bogor Indonesia was used as raw materials in this research. The objective of this research was to assess the potential of antibacterial activity of liverwort (M. paleacea). Maceration using 4 different solvents i.e ethanol, methanol, ethyl acetate, and hexane was used to extract the active compound. The potential of antibacterial activity of the extracts was assesed by agar diffusion method and direct-contact test by determining the minimum inhibitory concentration (MIC). The data showed that the ethanol extract had the biggest inhibition zone on three test bacteria. The inhibition zone and MIC were 10.8 mm and 0.7 mg/ml for S. aureus; 4.5 mm and 8.0 mg/ml for S. Typhimurium; 5.8 mm and 5.9 mg/ml for P. aeruginosa, respectively. The total phenol content of the extract was 22 mg/g. Phenolic, triterpenoid and flavonoid were positively detected in the extracts.